Food (In)security in the 2023 Kahramanmaraş Earthquake in Türkiye: Food Safety, Access, and Their Relationship with Nutritional Status - Cakir, Muhammet Ali; Mercan, Yeliz; Icyer, Necattin Cihat; Bozkurt, Fatih (Cambridge Univ Press, 2026)
Objective: This study examined the relationship between food safety, food access, and nutritional status among earthquake victims in Kahramanmara & scedil; and Hatay, T & uuml;rkiye. Methods: This descriptive, cross-sectional study was conducted face-to-face with 209 earthquake victims in 2023. Results: The median age was 42 years, and 52.6% were female. Among women, the perception of unhealthy food, inadequate mass feeding services, and dissatisfaction with meals increased the risk of food safety concerns. In men, those with an associate degree or higher were 20.7 times more likely to perceive food safety as inadequate, while the perception of unhealthy food raised this risk by 12.4 times. Lack of access to sufficient drinking water increased the risk of food inaccessibility by 2.6 times among women. In men, employment and dissatisfaction with meals increased this risk by 2.7 and 2.8 times, respectively. Both genders exhibited inadequate intake of water, energy, protein, polyunsaturated fats, fiber, folate, potassium, calcium, magnesium, iron, zinc, and several vitamins (P <0.05), while phosphorus and sodium levels were elevated (P <0.01). Conclusions: Food safety and access issues were critical among earthquake victims, significantly impacting nutritional status. Findings emphasize the need for improved emergency food aid and distribution systems to mitigate post-disaster nutritional risks.
Keywords: Disasters; Earthquakes; Food Supply; Food Insecurity; Nutritional Status